The value of augmentative and alternative communication strategies for adults with Broca's aphasia: a narrative literature review - Frade, Ana I. (2022)
Introduction: People with Broca’s aphasia have the right to language recovery and to communicate effectively. No literature review was found about the specific value of augmentative and alternative communication strategies to adults with Broca's aphasia. Aims: To explore current knowledge and update the understanding of the usefulness of augmentative and alternative communication strategies for adults with Broca’s aphasia. Material and method: A narrative literature review was developed based on the research question: What is the usefulness of augmentative and alternative communication for adults with Broca's aphasia? The research was carried out in the CINAHL and MEDLINE databases between January 8 and 21, 2021. Results: 16 articles were included, published between 2011 and 2020. Specific augmentative and alternative communication approaches (no-tech, low-tech, and high-tech), advantages, and factors that influence the effectiveness of this communication support were also identified. This review evidence that augmentative and alternative communication (mainly high-tech) is efficient in optimizing communication and in the language recovery of people with Broca’s aphasia. Conclusions: Augmentative and alternative communication should be employed in adults with Boca’s aphasia with two main aims: compensatory and restorative. High-technology strategies have a particularly positive impact.